2007
DOI: 10.1007/s00134-007-0804-y
|View full text |Cite
|
Sign up to set email alerts
|

Imipramine reverses the depressive symptoms in sepsis survivor rats

Abstract: The depressive symptoms evaluated by forced swimming test had been reversed after imipramine administration. Our data provide evidence that CLP-induced depressive symptoms are sensitive to antidepressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 10 publications
2
16
1
Order By: Relevance
“…The depressive symptoms evaluated by forced swimming task were reversed after imipramine administration. Our data provided evidence that CLP-induced depressive symptoms are sensitive to antidepressants [91].…”
Section: Depressive-like Symptoms and Anxiety-like Behaviorsupporting
confidence: 55%
“…The depressive symptoms evaluated by forced swimming task were reversed after imipramine administration. Our data provided evidence that CLP-induced depressive symptoms are sensitive to antidepressants [91].…”
Section: Depressive-like Symptoms and Anxiety-like Behaviorsupporting
confidence: 55%
“…The animals were subjected to CLP as previously described (Ritter et al 2003;Tuon et al 2007Tuon et al , 2008Comim et al 2008). Briefly, 74 rats (44 rats were subjected to CLP and 30 to Sham) were anesthetized with a mixture of ketamine (80 mg/kg) and xylazine (10 mg/kg) administered i.p.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, some reports have shown that sepsis survivor rats have symptoms of depression in the forced swimming task (Tuon et al 2008). Additionally, depressive-like behavior observed 10 days after cecal ligation and perforation (CLP) is reversed by classical antidepressant agent: imipramine (Tuon et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Imipramine, a standard antidepressant, was obtained from Novartis Pharmaceutical Industry (São Paulo, Brazil), and a dose of 10 mg/kg was injected intraperitoneally (i.p.) once a day over 21 days (Tuon et al 2007). Twelve hours after the last injection of BCAA, the animals were submitted to behavioral testing.…”
Section: Animalsmentioning
confidence: 99%